Error Probability Exponents and Achievable Region in Testing of Many Hypotheses for Two Independent Objects - Yessayan, Aram O.; Haroutunian , Evgueni A.; Hakobyan, Parandzem M. (Mathematical Problems of Computer Science, 2021)
The model of many hypotheses testing for one objects was examined by E. Tuncel. In the present work it is supposed that L hypothetical probability distributions are known and two objects independently each from other follow to one of them. N-vectors of values of discrete independent random variables represent results of N observations for each object. Decisions concerning realized probability distributions of the objects must be made on the base of such samples. It is proved that defined region for vector of error probability exponents “reliabilities for two objects completely characterizes set of all achievable vectors.